2020
DOI: 10.3389/fmicb.2020.579306
|View full text |Cite|
|
Sign up to set email alerts
|

Precise Species Identification and Taxonomy Update for the Genus Kluyvera With Reporting Kluyvera sichuanensis sp. nov.

Abstract: Kluyvera is a genus within the family Enterobacteriaceae and can cause various human infections but remains poorly studied. A carbapenem-resistant bla NDM−1-carrying Kluyvera strain 090646 T was isolated from a hospital sink in Chengdu, Sichuan province, China. Whole genome sequencing of the strain revealed that it had 28.2 to 42.3% in silico DNA-DNA hybridization (isDDH) scores and 84.15 to 90.10% average nucleotide identity (ANI) values with other Kluyvera species. Both values are well below the ≥ 70.0% isDD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 31 publications
5
7
0
Order By: Relevance
“…The resulting MLSA tree () strongly supported the inclusion of G163CM T within the genus Pseudocitrobacter , as it formed a monophyletic cluster with the two Pseudocitrobacte r type species, and other non-type strains. The MLSA tree displayed substantial higher confidence values for tree branches compared to the 16S rRNA tree and corroborated a previous results [2, 22], that Kluyvera is the sister genus to Pseudocitrobacter . The MLSA tree showed that G163CM T shared a more recent ancestor with P.…”
Section: Genome Featuressupporting
confidence: 89%
See 3 more Smart Citations
“…The resulting MLSA tree () strongly supported the inclusion of G163CM T within the genus Pseudocitrobacter , as it formed a monophyletic cluster with the two Pseudocitrobacte r type species, and other non-type strains. The MLSA tree displayed substantial higher confidence values for tree branches compared to the 16S rRNA tree and corroborated a previous results [2, 22], that Kluyvera is the sister genus to Pseudocitrobacter . The MLSA tree showed that G163CM T shared a more recent ancestor with P.…”
Section: Genome Featuressupporting
confidence: 89%
“…The higher phylogenetic resolution of the core tree based on a larger number of coding sequences, irrespective of amino acid or nucleotide level, indicates with greater confidence that P. vendiensis CPO20170097 T is closer to G163CM T . The core phylogenomic tree is consistent with the placement of the genus Pseudocitrobacter as sister group to the genus Kluyvera [2,22].…”
Section: Genome Featuressupporting
confidence: 71%
See 2 more Smart Citations
“…CCTCC M2018092 41 , Pantoea agglomerans 42 , Pseudomonas fulva 43 , P. putida 44 , Serratia marcescens 45 . Additional species may join the silage from animals, soil, or water: Acinetobacter gyllenbergii 46 , Citrobacter freundii 47 , Enterobacter asburiae 48 , E. cloacae 49 , E. roggenkampii 50 , E. sichuanensis 51 , Enterococcus faecalis 52 , Klebsiella aerogenes 53 , K. oxytoca 54 , Kluyvera intermedia 55 , Lactococcus garvieae 56 , Latilactobacillus curvatus 57 , Leclercia adecarboxylata 58 , Lelliottia amnigena 59 , Limosilactobacillus reuteri 28 , Providencia rettgeri 60 , Pseudescherichia vulneris 61 , Pseudomonas oryzihabitans 62 , Rhodopseudomonas palustris 63 , Serratia sp. SCBI 64 , Staphylococcus aureus 46 , S. kloosii 65 , S. pseudoxylosus 66 , S. saprophyticus 46 , Enterococcus faecium 52 .…”
Section: Discussionmentioning
confidence: 99%